KONSTRIBUSI KEKUATAN OTOT TUNGKAI DAN KESEIMBANGAN TERHADAP JAUHNYA TENDANGAN PADA PERMAINAN SEPAKBOLA SISWA SMP YAPIS CORDOVA TIMIKA INDONESIA - Kornelius Jehambur (SATRIA : Journal of Sports Athleticism in Teaching and Recreation on Interdisciplinary Analysis, 2022)
Physical ability is a part of the body that plays an important role in kicking a ball, such as elements of leg muscle strength, and balance which are very supportive things in order to be able to perform movements or skills to kick the ball well. Therefore, this study aims to determine how much the contribution of leg muscle strength and balance to the distance of the kick in the soccer game of the Yapis Cordova Indonesia Junior High School students in Timika. This study uses a correlation test (correlation research) to see the relationship between the independent variable and the dependent variable, where the independent variable consists of leg muscle strength and balance, while the dependent variable is the distance of the kick in the soccer game. Based on the analysis of the research results, the average score of leg muscle strength obtained by students was 39.10; the average score of balance is 71.33; and an average score of 35.38 away kicks. Meanwhile, the hypothesis test was obtained that the value of r = 0.691 was continued with the F test, it turned out that Fcount: 12.304 > Fttable: 3.35 with sig.0.000. These results indicate that the relationship between leg muscle strength and balance with kick distance is significant and the contribution of leg muscle strength to kick distance is 0.477 or 47.7%, so it can be concluded that there is a significant positive contribution between leg muscle strength and balance simultaneously on the distance of the kick. in the Yapis Cordova Indonesia Timika Junior High School student soccer game.